Fetal cyst reveling retroperitoneal enteric duplication - Imene Dahmane Ayadi; Ahlem Bezzine; Emira Ben Hamida; Zahra Marrakchi (Wolters Kluwer Medknow Publications, 2017)
Retroperitoneum is a very uncommon site of enteric duplication (ED). We report a new case of retroperitoneal ED cyst suspected in utero. Prenatal ultrasound showed an abdominal cystic mass. Noncommunicating retroperitoneal ED cyst measuring 70 mm × 30 mm was resected. Histopathologic examination confirmed the diagnosis.